Patterns of achievement-motivated behavior and performance as predictors for future success in rowing: A person-oriented study - Schmid, M. J.; Conzelmann, A.; Zuber, C. (International Journal of Sports Science & Coaching, 2021)
Talent selection in rowing is often solely based on anthropometric and performance variables, even though psychological characteristics are considered to be important contributors to successful talent development. Because multidimensional talent models and holistic theories represent the state-of-the-art in talent research, we aimed to find patterns connecting psychological and performance variables to future success in rowing. Therefore, 22 coaches rated the achievement-motivated behavior represented by the variables proactivity, ambition and commitment of 65 competitive to high-level athletes (Mage = 17.2 ± 1.55 years) for the past year (t1). Additionally, the athletes performed several 2,000 m ergometer tests during that same period. At t2 (30 months later), each rower`s performance was evaluated based on the success at different competitions. To examine the results, we used the person-oriented Linking of Clusters after removal of a Residue (LICUR) method to identify the relationships between the achievement-motivated behavior and ergometer results at t1 and the success at t2. The rowers could be assigned to five clusters. Although the highly motivated rowers were not the fastest on the ergometer at t1, they were more likely to be in highest performance level at t2 compared to the other clusters (OR = 3.5, p < .05). By contrast, all the ambitionless rowers and unmotivated rowers were either racing at national level or had dropped out. In conclusion, certain patterns of achievement-motivated behavior and current performance are associated with future success (30 months later). The consideration of achievement-motivated behavior in the selection of rowers seems promising in this context.